Two-Year Outcomes of Infants with Stage 2 or Higher Retinopathy of Prematurity: Results from a Large Multicenter Registry - Tolia, Veeral N.; Ahmad, Kaashif A.; Jacob, Jack; Kelleher, Amy S.; McLane, Nick; Arnold, Robert W.; Clark, Reese H.; for the MEDNAX ROP Registry Investigators (American Journal of Perinatology, 2020)
Objective To define the incidence of ophthalmologic morbidities in the first 2 years of life among infants diagnosed with stage 2 or higher retinopathy of prematurity (ROP).Study Design We prospectively enrolled premature infants with stage 2 or higher ROP. The infants were followed up for 2 years, and we report on data collected from outpatient ophthalmology and primary care visits.Results We enrolled 323 infants who met inclusion criteria, of which 112 (35%) received treatment with laser surgery (90) or bevacizumab (22). Two-year follow-up was available for 292 (90%) of the cohort. The most common ophthalmologic conditions at follow-up were hyperopia (35%), astigmatism (30%), strabismus (21.9%), myopia (19.2%), anisometropia (12%), and amblyopia (12%). Severe ophthalmologic morbidities such as retinal detachment and cataracts were rare, but occurred in both treated and untreated infants. Overall, 22.6% of the infants were wearing glasses at 2 years, including 8.5% of the untreated infants.Conclusion Patients with stage 2 or higher ROP remain at significant risk for ophthalmological morbidity through 2 years of age. Infants with regression of subthreshold ROP who do not require treatment represent an underrecognized population at long-term ophthalmological risk.ClinicalTrials.gov Identifier NCT01559571.
Keywords: retinopathy of prematurity; outcomes; premature infants; preterm infants